Influence of Voltage on Main Characteristics of Electric Lighting Lamps - V. B. Kozlovskaya; V. N. Radkevich; I. V. Kolosova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
An analysis and systemization of data on influence of voltage value on main lighting engineering, electric and economic characteristics of incandescent lamps, gaseous-discharge lamps of low and high pressure have been made in the paper.Analytical and graphical dependences have been obtained that ensure to evaluate quantitative changes of corresponding lamp characteristics at voltage deviation from nominal value.